2022
DOI: 10.1038/s41598-022-11974-3
|View full text |Cite
|
Sign up to set email alerts
|

Stratification at the health district level for targeting malaria control interventions in Mali

Abstract: Malaria is the leading cause of morbidity and mortality in Mali. Between 2017 and 2020, the number of cases increased in the country, with 2,884,827 confirmed cases and 1454 reported deaths in 2020. We performed a malaria risk stratification at the health district level in Mali with a view to proposing targeted control interventions. Data on confirmed malaria cases were obtained from the District Health Information Software 2, data on malaria prevalence and mortality in children aged 6–59 months from the 2018 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…The association between the complexity of infection and transmission intensity could also be driven by the difference in Anopheles vector densities between rural and urban dwellings (Bendixen et al, 2001). Previous studies have reported lower infection rates and vector densities in Bamako and Nioro compared to the other sites included in this study (Sissoko et al, 2017;Cissoko et al, 2022). Thus, Nioro had the least complex infections but also the shortest transmission season because it is bordering the Sahara.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…The association between the complexity of infection and transmission intensity could also be driven by the difference in Anopheles vector densities between rural and urban dwellings (Bendixen et al, 2001). Previous studies have reported lower infection rates and vector densities in Bamako and Nioro compared to the other sites included in this study (Sissoko et al, 2017;Cissoko et al, 2022). Thus, Nioro had the least complex infections but also the shortest transmission season because it is bordering the Sahara.…”
Section: Discussionmentioning
confidence: 56%
“…Faladje village is located 80 km northwest of Bamako with malaria transmission being both seasonal and perennial. Prevalence of parasitemia ranges from 40 to 50% of the population in the dry season (October–April) and 70–85% in the rainy season (May–September) ( Cissoko et al, 2022 ). The samples (216) spanned the decade from 2007 to 2017, with the largest number (125) from 2013.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations